COVID-19 related symptoms and vaccination usage among informal waste workers of Kathmandu, Nepal - Khanal, Ashish (International Journal of Occupational Safety and Health, 2023)
Introduction: About 56% of total population of Nepal have been fully immunized against COVID. But still foreign nationals and Informal Waste Workers (IWWs) outside of Nepal are struggling to get COVID vaccines. This study was intended to study the COVID-19 symptoms among IWWs of Kathmandu and the usage of vaccines by them. Methods: A Cross-sectional study was conducted among 107 IWWs of Kathmandu Valley from Balku, Sanepa, Kalimati and Teku areas. A convenience sampling method was used to find the respondents based on their willingness to participate in the study. Face-to-face interview was conducted using structured questionnaire to collect data from IWWs. Results: A total of 53.3% males and 46.7% females participated in this study. Despite of majority of waste workers facing COVID related symptoms, only 19.6% of waste workers had done COVID test. Around 77.6% of waste workers hadn’t still taken COVID vaccine with majority (93.9 %) of them belonging to India. Conclusion: The majority of IWWs of Kathmandu are afraid to take COVID vaccine. Despite of having COVID related symptoms, IWWs haven’t gone for COVID test. Though interested, the IWWs needs identity cards for vaccination which counts less number of waste workers being vaccinated.